The spatial and environmental distribution of the global eddy covariance tower network - Paul C. Stoy; Housen Chu; Emma Dahl; Daniela S. Cala; Victoria Shveytser; Susanne Wiesner; Ankur R. Desai; Kimberly A. Novick (International Journal of Biometeorology, 2026)
Eddy covariance has revolutionized our understanding of ecosystem-atmosphere interactions. Multiple studies have characterized the climate space occupied by flux tower networks, but none to our knowledge have characterized if eddy covariance sites represent the global distribution of soil characteristics that are critical for determining ecosystem function or studied the distances between towers to apply ‘paired’ tower studies. Of 1233 global eddy covariance towers explored here, half had a nearest neighbor within 10 km. Soil database pixels with towers have nearly 20% more silt and 8% less sand than the global soil texture distribution, with more soil N (0.58 g/kg vs. 0.38 g/kg) and organic C (8.3 g/kg vs. 5.4 g/kg), and 10% greater cation exchange capacity in upper layers than pixels without towers. Global syntheses of eddy covariance towers should be cognizant that tower networks capture more fertile soils than the terrestrial surface on average. A logical way to improve global representativeness is to further build collaborations and invest in underrepresented regions.

The intercorrelations between blood levels of ferritin, sCD163, and IL-18 in COVID-19 patients and their association to prognosis - Yuval Volfovitch; Avishai M. Tsur; Michael Gurevitch; Daniela Novick; Roy Rabinowitz; Mathilda Mandel; Anat Achiron; Menachem Rubinstein; Yehuda Shoenfeld; Howard Amital (Immunologic Research, 2022)

Informing Nature‐based Climate Solutions for the United States with the best‐available science - Kimberly A. Novick; Stefan Metzger; William R. L. Anderegg; Mallory Barnes; Daniela S. Cala; Kaiyu Guan; Kyle S. Hemes; David Y. Hollinger; Jitendra Kumar; Marcy Litvak; Danica Lombardozzi; Caroline P. Normile; et al. (Global Change Biology, 2022)
Nature‐based Climate Solutions (NbCS) are managed alterations to ecosystems designed to increase carbon sequestration or reduce greenhouse gas emissions. While they have growing public and private support, the realizable benefits and unintended consequences of NbCS are not well understood. At regional scales where policy decisions are often made, NbCS benefits are estimated from soil and tree survey data that can miss important carbon sources and sinks within an ecosystem, and do not reveal the biophysical impacts of NbCS for local water and energy cycles. The only direct observations of ecosystem‐scale carbon fluxes, for example, by eddy covariance flux towers, have not yet been systematically assessed for what they can tell us about NbCS potentials, and state‐of‐the‐art remote sensing products and land‐surface models are not yet being widely used to inform NbCS policymaking or implementation. As a result, there is a critical mismatch between the point‐ and tree‐scale data most often used to assess NbCS benefits and impacts, the ecosystem and landscape scales where NbCS projects are implemented, and the regional to continental scales most relevant to policymaking. Here, we propose a research agenda to confront these gaps using data and tools that have long been used to understand the mechanisms driving ecosystem carbon and energy cycling, but have not yet been widely applied to NbCS. We outline steps for creating robust NbCS assessments at both local to regional scales that are informed by ecosystem‐scale observations, and which consider concurrent biophysical impacts, future climate feedbacks, and the need for equitable and inclusive NbCS implementation strategies. We contend that these research goals can largely be accomplished by shifting the scales at which pre‐existing tools are applied and blended together, although we also highlight some opportunities for more radical shifts in approach.